A Comprehensive Review of Information Assurance in Cloud Computing Environments - Neoaz, Nahid (CV. Multi Kreasi Media, 2024)
IA is information that relates to the safety or insecurity of data and service that reside in the cloud computing spaces. Due to the benefits that are enshrined by cloud technologies organizations are using the cloud technologies as solutions to scalability, costs and flexibility while addressing issues of data privacy and security threats and compliance. It is for this reason that in this paper, the following aspects will be addressed; information assurance and cloud computing and other elements of information assurance such as CIA triad, authentication and non-repudiation. It also defines risk at the present time to mean data breach, insider threats, and Distributed Denial of Service (DDoS) attack among others; and how each of these organizations can pursue risk management strategies to such risks. In addition, this paper examines the data privacy aspect and the legal regulation of and concerns with cloud security in the shared responsibility model. By going through the organization information assurance plan, it is asserted that risk identification, assessment and monitoring, and information asset protection such us data encryption, and access should be acknowledged. Thus it becomes possible to implant sound security solution into the cloud computing solutions/ So by emulating on the best practices in support of the security/organizations gain all the benefits of Cloud computing. This paper gives a detailed insight of how Information assurance in cloud environment in a world that is going digital can be handled.